Cultural Acculturation of Ethnic Chinese and Ethnic Javanese in Kampung Ketandan Yogyakarta, 1966-2001 - Maghfirotull Fatkhiyah; Siska Nurazizah Lestari; Anggar Kaswati (Warisan: Journal of History and Cultural Heritage, 2024)
This study examines the cultural acculturation between Chinese and Javanese ethnic groups in Kampung Ketandan, Yogyakarta, during 1966-2001. The research aims to explore the factors driving and inhibiting this acculturation process. A historical method was employed, involving topic selection, heuristics, source verification, interpretation, and historiography. The findings reveal that the acculturation in Kampung Ketandan occurred harmoniously, marked by cultural adaptation processes such as deculturation, enculturation, acculturation, and assimilation manifesting in language, architecture, clothing, names, cuisine, and the arts. For example, the word "kecap" was adopted from Chinese, shop-house architecture became characteristic of Ketandan, the "kebaya encim" was integrated into local dress, and the Chinese-Javanese shadow puppetry emerged as a unique art form. Factors supporting acculturation included education, social contact, and a heterogeneous population, while barriers included ethnic prejudice and economic disparities. The study concludes that the acculturation in Kampung Ketandan fostered a rich and diverse cultural coexistence despite various challenges.